Synthesis and Preliminary Characterization of a PPE-Type Polymer Containing Substituted Fullerenes and Transition Metal Ligation Sites - Corinne A. Basinger; Kaitlin Sullivan; Sarah Siemer; Stuart Oehrle; Keith A. Walters (Journal of Chemistry)
A substituted fullerene was incorporated into a PPE-conjugated polymer repeat unit. This subunit was then polymerized via Sonogashira coupling with other repeat units to create polymeric systems approaching 50 repeat units (based on GPC characterization). Bipyridine ligands were incorporated into some of these repeat units to provide sites for transition metal coordination. Photophysical characterization of the absorption and emission properties of these systems shows excited states located on both the fullerene and aromatic backbone of the polymers that exist in a thermally controlled equilibrium. Future work will explore other substituted polyaromatic systems using similar methodologies.